Bone-Forming Capacity and Biodistribution of Bone Marrow-Derived Stromal Cells Directly Loaded into Scaffolds: A Novel and Easy Approach for Clinical Application of Bone Regeneration. Issue 10 (October 2015) - Léotot, Julie; Lebouvier, Angélique; Hernigou, Philippe; Bierling, Philippe; Rouard, Hélène; Chevallier, Nathalie
In the context of clinical applications of bone regeneration, cell seeding into scaffolds needs to be safe and easy. Moreover, cell density also plays a crucial role in the development of efficient bone tissue engineering constructs. The aim of this study was to develop and evaluate a simple and rapid cell seeding procedure on hydroxyapatite/ β-tricalcium phosphate (HA/βTCP), as well as define optimal cell density and control the biodistribution of grafted cells. To this end, human bone marrow-derived stromal cells (hBMSCs) were seeded on HA/βTCP scaffolds, and we have compared bone formation using an ectopic model. Our results demonstrated a significantly higher bone-forming capacity of hBMSCs directly loaded on HA/βTCP during surgery compared to hBMSCs preseeded for 7 days in vitro on HA/βTCP before ectopic implantation. The extent of new bone formation increases with increasing hBMSC densities quantitatively, qualitatively, and in frequency. Also, this study showed that grafted hBMSCs remained confined to the implantation site and did not spread toward other tissues, such as liver, spleen, lungs, heart, and kidneys. In conclusion, direct cell loading into a scaffold during surgery is more efficient for bone regeneration, as well as quick and safe. Therefore direct cell loading is suitable for clinical requirements and cell production control, making it a promising approach for orthopedic applications. Moreover, our results have provided evidence that the formation of a mature bone organ containing hematopoietic islets needs a sufficiently high local density of grafted hBMSCs, which should guide the optimal dose of cells for clinical use.